The Effect of Health Promotion Through Whatsapp Social Media on Adolescent Girls' Knowledge of Personal Hygiene with Symptoms of Vaginitis in SMP Negeri 1 Class IX Rupat Utara Regency Bengkalis in 2023 - Nurida, Nurida (Cattleya Darmaya Fortuna, 2024)
dolescent girls have a susceptibility to experiencing vaginitis if they do not maintain vaginal hygiene Vaginitis occurs in women who have entered the puberty phase or will enter the menopausal phase with risk factors in the form of lack of hygienic inflammation, unsafe sexual intercourse, with many partners, sexually transmitted diseases and others. Personal hygiene needs to be considered because it is related to the incidence of genital infections. The most frequent vaginitis is bacterial vaginosis, trichomoniasis and vulvovaginal candidiasis. This study aims to find out whether there is an effect of health promotion through whatsapp social media on the knowledge of class IX adolescent girls about personal hygiene with vaginitis symptoms at SMP Negeri 1 Rupat Utara, Bengkalis Regency in 2023. The type of research used is Pre-Experimental research. The population in the study is all adolescent girls in grade IX at SMP Negeri 1 Rupat Utara, Bengkalis Regency in 2023. The type of research used is Pre-Experimental research. The population in the study is all adolescent girls in grade IX at SMP Negeri 1 Rupat Utara, Bengkalis Regency in 2023. The sampling technique uses purposive sampling with a sample size of 41 people. using the Wilcoxon test. The results of the study obtained an average of knowledge before (7,561) and after (12,048). The results of the wilcoxon test were obtained p value = 0.000 < 0.05 which showed that there was an influence after being given health promotion through whatsapp social media about personal hygiene in adolescents at SMP Negeri 1 Rupat Utara, Bengkalis Regency. WhatsApp social media can be used as a reference for modern learning in conveying information to provide health promotion about personal hygiene with symptoms of vaginitis in adolescents to increase knowledge so that adolescents are prevented from vaginal diseases.